The Endothelial Protein C Receptor Is a Potential Stem Cell Marker for Epidermal Keratinocytes. (7th May 2017) - Xue, Meilang; Dervish, Suat; Chan, Benjamin; Jackson, Christopher J.
Abstract : Endothelial protein C receptor (EPCR) is a specific receptor for anticoagulant protein C and expressed by human epidermis and cultured keratinocytes. Here we investigated whether: (a) the level of EPCR in keratinocytes is associated with their growth potential; and (b) EPCR is a potential marker for human epidermal stem cells. Human keratinocytes isolated from foreskins or adult skin tissues were transfected with EPCR siRNA or EPCR overexpressing plasmids. Cell proliferation, long term proliferation potential, colony forming efficiency (CFE), and in vitro epidermal regeneration ability of EPCR high and EPCR l ° w cells were assessed. The expression and colocalization of EPCR with stem cell markers p63, integrin β1, and activation of MAP kinases were detected by flow cytometry, immunofluorescence staining, or Western blot. Results showed that EPCR was highly expressed by the basal layer of skin epidermis. EPCR high cells were associated with the highest levels of p63 and integrin β1. Most EPCR high cells were smaller in size, formed larger colonies and had a greater long term growth potential, CFE, holoclone formation, and in vitro epidermal regeneration ability when compared to EPCR l ° w cells. Blocking EPCR resulted in keratinocyte apoptosis, particularly in nondifferentiated conditions. Cell proliferation and p63 expression were reduced by blocking EPCR and enhanced by overexpressing this receptor. These data indicate that EPCR can regulate p63, is associated with highly proliferative keratinocytes, and is a potential human epidermal stem cell marker.